2019
DOI: 10.3390/nano9050728
|View full text |Cite
|
Sign up to set email alerts
|

Effect of AuPd Bimetal Sensitization on Gas Sensing Performance of Nanocrystalline SnO2 Obtained by Single Step Flame Spray Pyrolysis

Abstract: Improvement of sensitivity, lower detection limits, stability and reproducibility of semiconductor metal oxide gas sensor characteristics are required for their application in the fields of ecological monitoring, industrial safety, public security, express medical diagnostics, etc. Facile and scalable single step flame spray pyrolysis (FSP) synthesis of bimetal AuPd sensitized nanocrystalline SnO2 is reported. The materials chemical composition, structure and morphology has been studied by XRD, XPS, HAADFSTEM,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 69 publications
(85 reference statements)
0
14
0
Order By: Relevance
“…31 However, despite the advantages of such techniques over other nanomaterial production processes, only a few studies have reported H 2 sensing applications of flame-made nanomaterials including Pd-loaded SnO 2 films, 32 Pt-loaded WO 3 films, 33 and AuPd-sensitized nanocrystalline SnO 2 . 34 To the best of our knowledge, none have reported H 2 gas detection at room temperature using flame-made materials. On the other hand, recently, we have introduced a flame-driven approach for the synthesis of metal-decorated three-dimensional (3D) reduced graphene oxide (rGO) nanocomposites.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…31 However, despite the advantages of such techniques over other nanomaterial production processes, only a few studies have reported H 2 sensing applications of flame-made nanomaterials including Pd-loaded SnO 2 films, 32 Pt-loaded WO 3 films, 33 and AuPd-sensitized nanocrystalline SnO 2 . 34 To the best of our knowledge, none have reported H 2 gas detection at room temperature using flame-made materials. On the other hand, recently, we have introduced a flame-driven approach for the synthesis of metal-decorated three-dimensional (3D) reduced graphene oxide (rGO) nanocomposites.…”
mentioning
confidence: 99%
“…Flame technology is widely used in industry for the large-scale production of various nanomaterials including titanium dioxide, fumed silica, and carbon black, as it offers a continuous, economical, and one-step synthesis approach . However, despite the advantages of such techniques over other nanomaterial production processes, only a few studies have reported H 2 sensing applications of flame-made nanomaterials including Pd-loaded SnO 2 films, Pt-loaded WO 3 films, and AuPd-sensitized nanocrystalline SnO 2 . To the best of our knowledge, none have reported H 2 gas detection at room temperature using flame-made materials.…”
mentioning
confidence: 99%
“…However, the introduction of gold nanoparticles, on the contrary, shifts H 2 consumption peaks to the high-temperature region. This effect can be attributed [ 46 , 47 ] to the interaction of gold nanoparticles with surface oxygen vacancies on the SnO 2 surface and, as a consequence, the localization of chemisorbed oxygen species at the triple phase interface “Au-SnO 2 -gas”. Fujita et al [ 48 ] investigated the dependence of the effectiveness of CO conversion on M–O bond energy for Au/MO x catalysts.…”
Section: Resultsmentioning
confidence: 99%
“…If we consider printing technologies, the flexibility in design options, for deposition MOX gas-sensitive layers, become even wider. First, the high stability of the ceramic materials used in the developed microhotplate at high temperatures allows for the use of a wide range of technologies, up to the most extreme technological processes for synthesis MOX gas sensitive materials-for example, flame pyrolysis [42]. Additional flexibility is given by using a hot spot layout of microhotplate by a "circle" type, which allows the use of drop coating or inkjet printing technologies for the deposition of MOX for longterm stability and methods of deposition using screen printing [43].…”
Section: Discussionmentioning
confidence: 99%